The Study Of Metaphor Categories And The Translation Strategies Metaphors In Twilight - Lengari, Yoana Gita Pradnya; Maria Dimitrij Anggie Pavita (Pusat Riset dan Inovasi Nasional, 2023)
This paper discusses the metaphor categories and the translation strategies that are used in Twilight (2005) novel using Newark’s (1988) theory of metaphor categories and Larson’s (1984) theory of metaphor translation strategies. The acquired data consist of verbal data from Source Language (SL) text and Target Language (TL) text from both novels. This study is a qualitative study with note-taking technique library research, and observation. The library research and observation were applied to obtain information and evidence about the metaphor categories and the translation strategies used by the translator. The data then collected and noted using the note-taking technique, and there were 264 data gathered from SL and TL text which then analyzed to determine the categories and translation strategies of the metaphors. The analysis of the data then showed that dead metaphor is the main category that are found in SL and TL text with 172 data in SL text and 136 data in TL text. The next categories found is stock metaphor with 61 data in SL and 36 data in TL text, followed by cliché metaphor with 31 data in SL and 26 data in TL. There were no original, adapted, and recent metaphor categories found from the gathered data. In terms of metaphor translation strategies, there are four strategies used by the translator to translate metaphor as follows: (1) 150 data found translated using the strategy of metaphor/simile to metaphor/simile with the same image, (2) 9 data found translated using metaphor to simile strategy, (3) 56 data found translated by using metaphor to metaphor in the receptor language strategy, and (4) 150 data found translated using the strategy of metaphor to non-figurative language. The determination of metaphor categories and the translation strategies can help both the translator and the receptor language readers in a way that the categorization of the metaphor may assist the translator consider the most appropriate strategy to translate figurative language. Moreover, using the appropriate translation strategy can contribute to the accuracy, acceptability, and readability of the translation receptor language readers.